1987
DOI: 10.1021/bi00385a007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hyaluronate binding proteins isolated from 3T3 and murine sarcoma virus-transformed 3T3 cells

Abstract: A hyaluronic acid binding fraction was purified from the supernatant media of both 3T3 and murine sarcoma virus (MSV) transformed 3T3 cultures by hyaluronate and immunoaffinity chromatography. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis resolved the hyaluronate affinity-purified fraction into three major protein bands of estimated molecular weight (Mr,e) 70K, 66K, and 56K which contained hyaluronate binding activity and which were termed hyaluronate binding proteins (HABP). Hyaluronate affinity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 24 publications
0
56
0
3
Order By: Relevance
“…Preliminary in vitro studies have suggested potential roles for two molecularly distinct cell-surface receptors for HA, i.e., RHAMM and CD44 play pivotal roles in tumor invasion and metastasis (21,22). RHAMM was isolated originally from culture supernatants of ras-transformed murine 3T3 fibroblasts (23). In addition to its extracellular localization, RHAMM also has been shown to be an intracellular protein associated with extracellular-regulated kinase (ERK) and it plays an important role in transforming the activity of H-ras in fibroblasts (24).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary in vitro studies have suggested potential roles for two molecularly distinct cell-surface receptors for HA, i.e., RHAMM and CD44 play pivotal roles in tumor invasion and metastasis (21,22). RHAMM was isolated originally from culture supernatants of ras-transformed murine 3T3 fibroblasts (23). In addition to its extracellular localization, RHAMM also has been shown to be an intracellular protein associated with extracellular-regulated kinase (ERK) and it plays an important role in transforming the activity of H-ras in fibroblasts (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since HA binding domains are found in other ECM proteins including neurocan, versican/ CHAP, hyaluronectin, and aggrecan (Hardingham and Fosang, 1992;Laurent and Fraser, 1992;Rauch et al, 1992) it is conceivable that interference of HA binding to RHAMM alters HA interactions with other HA binding proteins. Conversely, RHAMM has been shown to bind to heparin, laminin, and collagen type IV, albeit with lower affinity than it binds to HA (Turley et al, 1987). Thus, anti-RHAMM antibodies and RHAMM peptides may affect neurite migration, in part, by interfering with interactions of RHAMM with other ECM components shown to affect neurite outgrowth (Carbonetto et al, 1983;Bozyczko and Horwitz, 1986;Carri et al, 1988;Dow et al, 1993).…”
Section: Neurite Extension and Motilitymentioning
confidence: 99%
“…Hyaluronic acid (HA) is an abundant component of the extracellular matrix. Three receptors for HA on the cell surface, namely CD44 (Aru o et al, 1990), RHAMM (Turley et al, 1987) and LYVE (Banerji et al, 1999), have been identiÂźed. CD44, the principal cellular surface receptor for hyaluronic acid, comprises a family of many isoforms (85 ± 200 kDa) that arise through alternative splicing of the preRNA and di erent degrees of glycosylation (Naor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%